Spectacular Wealth: The Festivals of Colonial South American Mining Towns - Voigt, Lisa (University of Texas Press, 2016)
Bridging print culture and performance, Spectacular Wealth draws on eighteenth-century festival accounts to explore how colonial residents of the silver-mining town of Potosí, in the viceroyalty of Peru, and the gold-mining region of Minas Gerais, in Brazil, created rich festive cultures that refuted European allegations of barbarism and greed. In her examination of the festive participation of the towns’ diverse inhabitants, including those whose forced or slave labor produced the colonies’ mineral wealth, Lisa Voigt shows how Amerindians, Afro-descendants, Europeans, and creoles displayed their social capital and cultural practices in spectacular performances.Tracing the multiple meanings and messages of civic festivals and religious feast days alike, Spectacular Wealth highlights the conflicting agendas at work in the organization, performance, and publication of festivals. Celebrants and writers in mining boomtowns presented themselves as far more than tributaries yielding mineral wealth to the Spanish and Portuguese empires, using festivals to redefine their reputations and to celebrate their cultural, spiritual, and intellectual wealth.